EFEKTIVITAS PEMBELAJARAN SENAM PADA PRODI PJKR FIK UNY - Farida Mulyaningsih (Jurnal Pendidikan Jasmani Indonesia, 2008)
The gymnastic teaching at Physical Education, Health, and Recreation Study Program, UNY had been dominated by command and tasking approach. As a result, the expected goals were not effective so that there was a need to inovate learning model. This research aimed at improving advanced gymnastic learning process using resiprocal and inclusion approach. This research was a Classroom Action Research (CAR). A number of 62 students taking gymnastic class in 2001/2002 were participated in this research. It employed observation sheets resiprocal and inklusion teaching style and questionaire to investigate students voice. The data was analyzed by using descriptive statistics. This research concluded that inclusion and resiprocal approaches were very effective for teaching gymnastic and students voice was also positive. Kata-kata kunci: Gaya mengajar, senam